Bioefficacy of synthetic and botanical insecticides for controlling podborer (Helicoverpa armigera) and podfly (Melanagromyza obtusa) infesting vegetable purpose pigeonpea (Cajanus cajan) - PATEL, J J; PATEL, N C; JAYANI, D B; PATEL, J R; PATEL, B D (The Indian Journal of Agricultural Sciences, 2013)
A field expeliment was conducted during rainy season (kharif) 1993 and 1994 to find out an effective and economical insecticide for controlling podborer (Helicoverpa armigera Hubner), plume moth (Marasmarcha liophanes Mey) and podfly (Melanagromyza obtusa Malloch) on vegetable - purpose pigeonpea [Cajanus cajan (L.) Millsp.]. Endosulfan Ec 0.035% (1: 14.18) gave the highest incremental cost: benefit ratio, followed by endosulfan WP 0.035% (1 : 12.95) and chlorpyriphos 0.02%. Neem - seed - kernel suspension (NSKS) 3%, though gave 1 : 11.77 cost: benefit ratio, was less effective and economical for controlling these insects